Efficient heterogeneous polyoxometalate-hybrid catalysts for the oxidative desulfurization of fuels - Mirante, Fátima (2018)
The heterogenization of the highly active monovacant polyoxotungstate ([PW11O39](7-), abbreviated as PW11) was achieved by preparing the corresponding long chain quaternary ammonium salt (ODA(7)PW(11), ODA = CH3(CH2)(17)(CH3)(3)N). The complete cation exchange confers total heterogeneity to the monovacant catalyst while keeping its oxidative catalytic activity. In fact, the heterogeneous catalyst allowed for the complete desulfurization of a multicomponent model diesel (2000 ppm S) after 40 min of reaction, conciliating extraction (using BMIMPF6 solvent) and oxidation (ECODS process using H2O2 oxidant). The heterogeneous catalyst has shown a superior desulfurization performance when compared with the homogeneous quaternary ammonium TBAPW(11) catalyst (TBA = (C4H9)(4) N). Both hybrid catalysts have been successfully reused in consecutive ECODS cycles. Additionally, the long carbon chain cations provide a protective environment around the polyoxometalate allowing for ODA(7)PW(11) to retain its heterogeneity and structure after the ECODS process.